A preparation process and equipment for producing nano spinel by harmless treatment of aluminum ash
The described process addresses the issue of insufficient refractoriness and heavy metal pollution in aluminous spinel production by pretreating aluminum ash to remove harmful substances, enhancing product performance and environmental sustainability.
Patent Information
- Application Number
- CN202411289963.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Existing methods for producing aluminous spinel from secondary aluminum ash result in insufficient refractoriness and heavy metal pollution due to the direct use of aluminum ash, which contains toxic and harmful substances like fluoride, cyanide, and heavy metal oxides, leading to poor product performance and environmental contamination.
A process involving pretreatment of aluminum ash to remove halogen salts and heavy metals, followed by batching with starch, nano metal oxides, and pH adjustment, then air washing and calcination to produce nano-spinel with improved refractoriness, utilizing waste heat for energy efficiency.
The process effectively removes harmful substances, enhances the refractoriness of nano-spinel, and reduces environmental impact while saving energy and costs, resulting in a more stable and efficient production method.
Smart Images

Figure CN118791297B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, and in particular to a preparation process and equipment for producing nano spinel by harmless treatment of aluminum ash. Background Art
[0002] Aluminous spinel is an important chemical raw material, widely used in ceramics, refractory materials and abrasives. Its chemical composition is mainly aluminum oxide (Al2O3) and other oxides such as magnesium, zinc and iron. It has excellent high temperature resistance, corrosion resistance and wear resistance. Due to its unique physical and chemical properties, aluminous spinel plays an indispensable role in modern industry.
[0003] Aluminous spinel is widely used in the production of refractory bricks and lining materials for high-temperature kilns, such as castables, monolithic refractory materials and refractory fibers, due to its excellent high-temperature resistance. These refractory materials can withstand temperatures up to 1800 degrees Celsius, ensuring the stability and safety of the kiln during long-term operation. In addition, aluminous spinel also has good thermal shock resistance, allowing it to remain stable in an environment with frequent temperature changes.
[0004] The aluminum-containing spinel materials prepared by conventional processes mostly use high-purity aluminum-containing compounds and other element compounds, such as CN103449503A, a method for preparing nano zinc aluminum spinel. Its preparation method is to add zinc salt to water to dissolve, add aluminum source, stir for 10 to 30 minutes, add pore expander, stir, age at 20 to 100 ° C for 30 to 60 minutes, dry, and roast at 500 to 1200 ° C; the raw material molar ratio is Zn: Al: water = 1: 2: 16 to 35; the amount of pore expander added is 0.5 to 30% based on the mass of zinc oxide as 100%; the pore expander is one or more of sucrose, glycerol, ammonium carbonate, ammonium bicarbonate, polystyrene emulsion, polyethylene glycol; Liu Minsheng, Ma Aiqiong, Wang Zhen published a paper entitled "The Effect of Al2O3 Raw Material Type on the Synthesis of Zinc Aluminum Spinel by Solid Phase Reaction Method" and other papers are all prepared by pure compounds, and the production cost is relatively high.
[0005] Secondary aluminum ash, also known as black ash, is mainly the waste after the extraction of metallic aluminum from primary aluminum ash or the aluminum-containing waste slag produced in the aluminum refining process. Secondary aluminum ash is a hazardous waste, which contains a large amount of toxic and harmful substances such as fluoride, cyanide, aluminum carbide, aluminum amide, etc. The alumina content in secondary aluminum ash is usually around 60%, and it also contains toxic and harmful substances such as fluoride salts, chlorides and other heavy metal oxides; AlN and Al4C3 produce NH3 and CH4 and other gases in contact with water, which have a foul smell. Fluoride and cyanide will dissolve in water and pollute natural water bodies, and need to be harmlessly treated. CN105294135A proposes a method for directly preparing aluminum spinel refractory materials using aluminum ash and the materials prepared therefrom. The technical scheme is as follows: 50-90wt% of aluminum ash is mixed with 10-50wt% of raw materials containing magnesium or zinc, and 0.1-0.5wt% of sintering aid is added to the mixture, ball milling is performed to mix and then molded, and the molded body is heated to 1000-1400℃ at a heating rate of 2-10℃ / min in a high-temperature reaction furnace, kept warm for 1-5h, and then cooled to room temperature to obtain aluminum spinel refractory material. Aluminum ash solid waste is used as raw material, and the raw material has a wide range of application, which better solves the problem of comprehensive utilization of aluminum ash and its secondary pollution to the environment. However, the components in aluminum ash are complex, and the direct use of aluminum ash will cause insufficient product performance, such as insufficient refractoriness, expansion of heavy metal pollution, and other problems. CN115947611B relates to a method for preparing refractory materials from secondary aluminum ash. The preparation method provided by the present invention classifies the direction of resource application of secondary aluminum ash. When the mass percentage of silicon dioxide in the secondary aluminum ash is less than 5%, it can be used to prepare alkaline alkaline magnesium-aluminum refractory materials; when the mass content of silicon dioxide in the secondary aluminum ash is ≥5%, it can be used to prepare acidic acidic magnesium-aluminum-silica refractory materials. The present invention classifies the secondary aluminum ash and obtains refractory materials through one-step sintering. The method provided by the present invention classifies the secondary aluminum ash, and while reducing the processing cost of the secondary aluminum ash, one-step sintering is adopted, and the low-cost harmless disposal and resource utilization of the secondary aluminum ash are realized at the same time, which simplifies the processing steps of the secondary aluminum ash, realizes energy conservation and emission reduction, and the prepared refractory materials have the characteristics of high density and can be widely used in the field of refractory materials. However, it does not exclude the heavy metals and halide salts therein, which still causes insufficient product performance, such as insufficient refractoriness, expansion of heavy metal pollution and other problems. Summary of the invention
[0006] In order to solve the above problems, the present invention proposes a preparation process and equipment for producing nano-spinel by harmless treatment of aluminum ash, which can effectively remove halogen salts and heavy metals in aluminum ash, so that the nano-spinel material has better refractoriness; it is energy-saving and environmentally friendly, makes full use of waste heat resources, improves energy utilization efficiency, and saves costs.
[0007] To achieve the above object, the technical solution of the present invention is:
[0008] A preparation process for producing nano spinel by harmless treatment of aluminum ash comprises the following steps:
[0009] Step (1) aluminum ash pretreatment: aluminum ash and water are added into a pretreatment barrel at a mass ratio of 1:10-15, stirred for reaction for 2-3 hours, and then dehydrated for the first time. After the first dehydration, the solid content is 85-90%, and the pretreated material is obtained;
[0010] Step (2) batching: pour the pretreated material into a batching barrel, add 1-5% starch, 30-60% nano metal oxide particles, 10-15% aluminum sulfate, and 30-45% sodium aluminate based on the aluminum ash weight, add water to a solid content of 8-10%, add a pH adjuster, adjust the pH to 6-8, stir for 5-10 minutes, pass into a ball mill, add water, and mill for 1-3 hours, and obtain a secondary dehydrated material after a second dehydration;
[0011] Step (3) air washing molding: introducing carbon dioxide into the secondary dehydrated material, followed by extrusion molding, and obtaining a green body after drying;
[0012] Step (4) calcination: the green body is sent to a calcination device for calcination, and the nano spinel material is obtained after cooling.
[0013] The aluminum ash pretreatment process can remove most of the aluminum nitride, chloride, and fluoride in the aluminum ash. For example, under high temperature conditions, chloride salts will react with oxygen in the furnace to generate chlorine. The chemical reaction between chlorine and refractory materials is one of the main reasons for the damage of spinel refractory bricks. As a strong oxidizing gas, chlorine may react chemically when in contact with spinel refractory bricks, causing the brick body to slag, thereby affecting its structure and performance. This chemical reaction will not only damage the surface of the spinel refractory bricks, but may also penetrate into the interior of the brick body, causing deeper damage. In addition, the intrusion of chlorine will also aggravate the effects of thermal shock and mechanical wear, further accelerating the damage process of the brick body.
[0014] In this scheme, a hydrolysis reaction AlN+H2O→NH3+Al(OH)3 occurs during the pretreatment process, and the reaction is accelerated in a hot water environment. After the first dehydration, most of the halogen salts in the pretreatment material have been removed, increasing the aluminum content in the aluminum ash. And because most halogen salts are acidic salts, the decomposed AlN and the generated ammonia can neutralize the pH of the water in the pretreatment barrel to generate a variety of metal precipitates such as Al(OH)3, Fe(OH)3, and Zn(OH)2. These precipitates are dispersed in the material during the ball milling process, providing active sites for the subsequent solid phase reaction to generate nano spinel.
[0015] In step (2), the pre-treated material is diluted with water and ball-milled for four main purposes: 1. Improving fluidity and dispersibility, providing guarantee for the uniformity of ingredients; 2. Aluminum sulfate and sodium aluminate are added, and the double hydrolysis reaction can generate fine nano-Al(OH)3 during the ball-milling process of the material, improving the reaction activity; 3. The ball-milling process mixes the aluminum ash and nano-oxide composite particles at a microscopic scale, which is conducive to the occurrence of solid-phase reaction; 4. Further dissolves the halogens remaining in the aluminum ash agglomerate and discharges them in the second dehydration. Starch has three main functions: 1. Acts as a binder in subsequent molding; 2. Acts as a pore-forming agent. Starch will decompose during the calcination process, leaving pores, so that the nano-spinel material obtains uniform and fine micropores; 3. Starch particles act as a condensation nucleus, which is conducive to secondary dehydration.
[0016] In step (3), the gas washing is mainly used to adjust the pH of the secondary dehydrated material and neutralize the small amount of ammonia generated in step (2) that has not overflowed; a small amount of carbonate is formed to provide micropores for calcining the nano-spinel material.
[0017] Preferably, in step (1), the nano metal oxide particles are one or more of nano magnesium oxide, nano zinc oxide, nano manganese oxide, and nano iron oxide.
[0018] In specific operations, the properties of the final nano-spinel material can be adjusted by adding different proportions of nano-metal oxide particles.
[0019] Preferably, in step (2), the pH adjuster is citric acid and sodium citrate.
[0020] In step (2), pH adjustment is to make the hydrolysis reaction more complete, and citric acid is used to remove harmful heavy metal elements during the second dehydration process. In addition to adjusting the pH of the buffer, in an acidic environment, citrate can also complex some harmful heavy metal elements, and remove heavy metal elements during the subsequent dehydration process after adding flocculants.
[0021] Although the particle size of the material system after ball milling is small, there is a large amount of Al(OH)3 in the system, which acts as a flocculant, causing the material to agglomerate and facilitate dehydration.
[0022] Preferably, the secondary dehydration method is centrifugal dehydration, and the water content of the secondary dehydrated material is 5-10%.
[0023] Preferably, in step (3), the drying process is: drying at 50-60°C until the water content is less than 2%.
[0024] If the moisture content of the green body is too high, it is easy to crack during calcination. In this solution, the green body is first dried to a moisture content of less than 2%, and then sent to the calcination equipment for calcination. The calcination equipment can be any equipment that can meet the calcination temperature requirements, such as a rotary kiln, an electric kiln, etc.
[0025] Preferably, the calcination process in step (4) is as follows: heating from room temperature to 300°C at a rate of 3-5°C / min, heating from 300 to 1000°C at a rate of 5-8°C / min, heating from 1000 to final temperature at a rate of 8-15°C / min, and keeping warm for 10-30 minutes; the final temperature is 1250-1550°C.
[0026] Preferably, in step (4), the cooling rate is 0.5-5°C / s.
[0027] Too fast cooling rate, especially just after calcination, will lead to dark cracks, or even direct cracking and scrapping. Dark cracks may be caused by the large difference in contraction between the glass phase on the grain and the grain boundary caused by too fast cooling rate.
[0028] The temperature is increased at a rate of 3-5°C / min from room temperature to 300°C in order to fully discharge the residual moisture in the green body and prevent cracking caused by moisture; in the 300-1000°C temperature range, most hydroxides and carbonates are decomposed, and the temperature is increased at a rate of 5-8°C / min to ensure uniform overflow of gas or moisture and obtain a good micropore distribution effect; the temperature is increased at a rate of 8-15°C / min from 1000 to the final temperature in order to rapidly nucleate and increase the number of nuclei. At the same time, the holding time should not be too long to prevent excessive growth of grains or excessive enlargement of micropores beyond the nanoscale.
[0029] A device for the preparation process of producing nano spinel by harmless treatment of aluminum ash, the device comprises: a pretreatment barrel, a first dehydrator, a batching barrel, a ball mill, a second dehydrator, an air washing component, a molding device, a drying device, a calcining device, and a cooling device, which are connected in sequence according to the material flow order of the nano spinel preparation process.
[0030] The material flow process of the preparation process of producing nano spinel by harmless treatment of aluminum ash described in this scheme is as follows: the aluminum ash enters the pretreatment barrel, passes into the first dehydrator after treatment, enters the batching barrel after dilution after the first dehydration, enters the ball mill after batching, enters the second dehydrator after ball milling, enters the air washing part after the second dehydration, then enters the molding equipment, enters the drying equipment after molding, enters the calcining equipment after drying, enters the cooling equipment after calcination, and obtains the finished product after cooling. The material flow between the above parts, that is, the connection between the equipment is realized through conventional pipelines, augers or conveying equipment.
[0031] Preferably, the pretreatment barrel includes a barrel body, a hot air pipe, an exhaust gas collection port, a feed port and an outlet port, the hot air pipe surrounds the barrel body, the feed port is arranged at the upper end of the barrel body, and the outlet port is arranged at the bottom of the barrel body; the exhaust gas collection port is arranged at the top of the barrel body.
[0032] Preferably, the hot air duct includes an air inlet connected to a cooling device and an air outlet connected to a drying device.
[0033] Preferably, the hot air pipe is a semicircular pipe welded to the barrel body.
[0034] Preferably, the air washing component comprises a horizontal auger connected to the second dehydrator and a cylinder connected to the forming equipment, and the horizontal auger is connected to the cylinder by welding; and a vent hole is provided at the bottom of the cylinder.
[0035] Hot water can promote the reaction. This scheme designs the pretreatment barrel. A semicircular tube surrounding the cylinder is welded on the surface of the pretreatment barrel, that is, the cylinder itself is the wall of the hot air duct. This scheme cools the calcined nano-spinel material by air cooling. The air enters the cooling device from the discharge end of the nano-spinel material to cool the nano-spinel material, and this process heats the air. The heated hot air is introduced from the feed end of the cooling device into the hot air duct surrounding the cylinder through the air inlet of the hot air duct. The flow process of hot air in the hot air duct can heat the water in the pretreatment barrel, promote the occurrence of hydrolysis reaction, and release ammonia at the same time. This design also makes full use of waste heat and saves energy. The hot air duct extracts the hot air in the cooling device through the induced draft device. By controlling the air flow rate of the hot air duct, the cooling rate in the cooling device and the drying rate in the drying device can be controlled. Considering that the high temperature section of the cooling device is the connection section with the calcining furnace, the cooling rate here should not be too fast, otherwise it is easy to produce dark cracks or even direct cracking. Therefore, the hot air pipe flow rate should be controlled at 1-4m 3 / S.
[0036] In order to prevent the material from settling and hardening, the pretreatment barrel can also be equipped with some agitators, ultrasonic equipment, etc. Among them, the ultrasonic equipment can also promote the reaction. The air outlet of the hot air pipe is connected to the drying equipment of the green body. The air outlet temperature is still around 70°C and is relatively dry, which can be used to dry the green body (the drying temperature of the green body is about 50-70°C, and it takes about 30-60 minutes to dry the moisture of the body to 1-2%).
[0037] The secondary dehydrated material enters the horizontal auger of the air washing component, is transported toward the cylinder through the horizontal auger, and then enters the molding equipment through gravity. Carbon dioxide gas enters from the bottom of the cylinder, flows into the horizontal auger along the cylinder, and escapes in the second dehydrator. During this process, the horizontal auger can drive the material to turn over, so that the carbon dioxide can fully contact with the secondary dehydrated material, improving the reaction efficiency.
[0038] Compared with the existing technology, the advantages of this solution are:
[0039] In terms of technology: by effectively removing the halogen salts and heavy metals in the aluminum ash during pretreatment, the aluminum ash of the spinel solid phase reaction has a more controlled composition; starch is added as a binder and pore-forming agent, which can react completely during calcination without introducing new elements. At the same time, the starch particles act as a condensation nucleus, which is conducive to secondary dehydration; the pH of the secondary dehydrated material is adjusted through the air washing process, and a small amount of carbonate is introduced to provide more microporous structures for the calcined nano-spinel material, thereby improving the thermal insulation effect; the design of the calcination process can adjust the micropores and grain size in the nano-spinel material, so that the nano-spinel material has better refractoriness;
[0040] On the equipment: the waste heat from cooling is used to heat the pretreatment barrel, and then the green body is dried, which fully utilizes the waste heat and has the effect of energy saving and environmental protection; an air washing device is designed to achieve pH and composition adjustment during the transportation of secondary dehydrated materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 It is a schematic diagram of the equipment of the present invention.
[0043] Figure 2 This is a structural diagram of the pretreatment barrel of the present invention.
[0044] Figure 3 It is a cross-sectional view of the structure diagram of the pretreatment barrel of the present invention.
[0045] Figure 4 It is a structural diagram of the air washing component of the present invention.
[0046] Figure 5 It is a cross-sectional view of the gas washing component of the present invention.
[0047] In the figure: 1. pretreatment barrel, 2. first dehydrator, 3. batching barrel, 4. ball mill, 5. second dehydrator, 6. air washing component, 7. molding equipment, 8. drying equipment, 9. calcining equipment, 10. cooling equipment, 1-1. tail gas collection port, 1-2 feed port, 1-3 hot air duct, 1-3-1 air inlet, 1-3-2 air outlet, 1-4 discharge port, 1-5 barrel body, 6-1 cylinder body, 6-2 horizontal auger, 6-3 air vent, 6-4 second dehydrator discharge port, 6-5 molding equipment feed port. DETAILED DESCRIPTION
[0048] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1, a preparation process for producing nano spinel by harmless treatment of aluminum ash, combined with Figure 1 As shown, the following steps are included:
[0050] Step (1) aluminum ash pretreatment: aluminum ash and water are added into a pretreatment barrel 1 at a mass ratio of 1:15, stirred for reaction for 3 hours, and then dehydrated for the first time by a first dehydrator 2. After the first dehydration, the solid content is 90%, and a pretreated material is obtained;
[0051] Step (2) batching: pour the pretreated material into a batching barrel 3, add 3% starch, 45% nano metal oxide particles, 12% aluminum sulfate, and 30% sodium aluminate based on the aluminum ash weight, add water to a solid content of 8%, add pH citric acid to adjust the pH to 7, stir for 8 minutes, pass into a ball mill 4, add water, and ball mill for 2 hours, and dehydrate for a second time in a second dehydrator 5 to obtain a secondary dehydrated material with a water content of 8%;
[0052] Step (3) air washing molding: the secondary dehydrated material enters the air washing component 6, carbon dioxide is introduced into the secondary dehydrated material, and then enters the molding device 7 for extrusion molding. After molding, it enters the drying device 8 and is dried at 60° C. to a green body with a water content of 1.5%;
[0053] Step (4) Calcination: The green body is sent to a calcination device 9 for calcination. The calcination process is as follows: the temperature is increased from room temperature to 300°C at a rate of 3°C / min, from 300 to 1000°C at a rate of 5°C / min, and from 1000 to 1350°C at a rate of 12°C / min, and the temperature is kept at this temperature for 30 minutes. After the calcination is completed, the green body is sent to a cooling device 10, and cooled at a cooling rate of 1°C / s to obtain a nano spinel material.
[0054] The nano metal oxide particles are nano magnesium oxide, nano zinc oxide and nano manganese oxide in a mass ratio of 1:1:1.
[0055] like Figure 2The figure shows the structure of the pretreatment barrel 1 of the present invention. The pretreatment barrel 1 includes a barrel body 1-5, a hot air pipe 1-3, a tail gas collecting port 1-1, a feed port 1-2 and a discharge port 1-4. The hot air pipe 1-3 surrounds the barrel body 1-5, the feed port 1-2 is arranged at the upper end of the barrel body 1-5, and the discharge port 1-4 is arranged at the bottom of the barrel body 1-5; the tail gas collecting port 1-1 is arranged at the top of the barrel body 1-5. Aluminum ash enters the barrel body 1-5 from the feed port 1-2, and the aluminum ash pretreatment reaction of step (1) is carried out in the barrel body 1-5. The ammonia and other tail gases generated after the reaction are centrally treated through the tail gas collecting port 1-1, and the discharge port 1-4 after the reaction is completed enters the first dehydrator 2. Figure 3 As shown, combined Figure 1 It can be seen that the air inlet 1-3-1 of the hot air pipe 1-3 is connected to the cooling device 10, and the air outlet 1-3-2 is connected to the drying device 8. The hot air pipe 1-3 is a semicircular pipe welded to the barrel body 1-5. The air inlet 1-3-1 of the hot air pipe 1-3 is connected to the cooling device 10. The hot air in the cooling device 10 enters the hot air pipe 1-3 from the air inlet 1-3-1 of the hot air pipe 1-3. The hot air pipe 1-3 surrounds the barrel body 1-5. The hot air in the hot air pipe 1-3 can heat the barrel body 1-5, thereby increasing the temperature of the water in the pretreatment barrel 1 and promoting the reaction. The hot air in the hot air pipe 1-3 enters the drying device 8 from the air outlet 1-3-2 after being heated by the barrel body 1-5, which can just meet the temperature required for drying the green body, and the energy efficiency is relatively high.
[0056] like Figure 4 , Figure 5 As shown, the air washing component 6 includes a horizontal auger 6-2 connected to the discharge port 6-4 of the second dehydrator and a barrel 6-1 connected to the feed port 6-5 of the molding device. The horizontal auger 6-2 is connected to the barrel 6-1 by welding. The bottom of the barrel 6-1 is provided with a vent 6-3, and carbon dioxide enters the air washing component 6 through the vent 6-3. The secondary dehydrated material obtained after secondary dehydration by the second dehydrator 5 enters the horizontal auger 6-2 at the discharge port 6-4 of the second dehydrator. Since the air washing component 6 is passed with carbon dioxide gas, the horizontal auger 6-2 transports the secondary dehydrated material to flip it and push it forward. The secondary dehydrated material can fully contact the carbon dioxide until it falls into the barrel 6-1. Falling into the barrel 6-1 means entering the feed port 6-5 of the molding device, and then being molded in the molding device 7.
[0057] Example 2 is different from Example 1 in that, in step (1), the mass ratio of aluminum ash to water is 1:10; in step (2), 1% starch, 60% nano-metal oxide particles, 10% aluminum sulfate, and 40% sodium aluminate are added to the weight of the aluminum ash.
[0058] Example 3 is different from Example 1 in that, in step (2), 5% of starch, 60% of nano metal oxide particles, 15% of aluminum sulfate, and 40% of sodium aluminate are added to the aluminum ash weight; in step (4), the calcination process is: heating from room temperature to 300°C at a rate of 5°C / min, heating from 300 to 1000°C at a rate of 8°C / min, heating from 1000 to 1550°C at a rate of 15°C / min, and keeping warm for 10 minutes; the cooling rate is 5°C / s.
[0059] Comparative Example 1 is different from Example 1 in that no pretreatment is performed, specifically:
[0060] Step (1) batching: in a batching barrel 3, aluminum ash is mixed with 3% starch, 45% nano-metal oxide particles, 12% aluminum sulfate, and 30% sodium aluminate in an amount based on the weight of the aluminum ash, water is added to a solid content of 8%, pH citric acid is added to adjust the pH to 7, the mixture is stirred for 8 minutes, the mixture is passed into a ball mill 4, water is added, and the mixture is ball-milled for 2 hours, and the mixture is dehydrated for a second time by a second dehydrator 5 to obtain a secondary dehydrated material having a water content of 8%;
[0061] Step (2) air washing molding: the secondary dehydrated material enters the air washing component 6, carbon dioxide is introduced into the secondary dehydrated material, and then enters the molding device 7 for extrusion molding. After molding, it enters the drying device 8 and is dried at 60° C. to a green body with a water content of 1.5%;
[0062] Step (3) Calcination: The green body is sent to a calcination device 9 for calcination. The calcination process is as follows: room temperature-300°C at a rate of 3°C / min, 300-1000°C at a rate of 5°C / min, 1000-1350°C at a rate of 12°C / min, and heat preservation for 30 minutes. After calcination, the green body is sent to a cooling device 10 and cooled at a cooling rate of 1°C / s to obtain a nano spinel material.
[0063] The nano metal oxide particles are nano magnesium oxide, nano zinc oxide and nano manganese oxide in a mass ratio of 1:1:1.
[0064] Comparative Example 2 is different from Example 1 in that no air washing is performed, that is, the vent hole 6-3 is closed.
[0065] Comparative Example 3 is different from Example 1 in that citric acid or citrate is not used for pH adjustment, but acetic acid and sodium bicarbonate are selected as pH adjusters.
[0066] Comparative Example 4 is different from Example 1 in that no starch is added to the ingredients in step (2).
[0067] Comparative Example 5 is different from Example 1 in that the cooling rate is 8° C. / s.
[0068] Comparative Example 6 is different from Example 1 in that, in step (3), the green body is sent to a calcination device 9 for calcination. The calcination process is as follows: heating from room temperature to 300°C at a rate of 6°C / min, heating from 300 to 1000°C at a rate of 3°C / min, and heating from 1000 to 1350°C at a rate of 3°C / min, and keeping warm for 1 hour. After the calcination is completed, the green body is sent to a cooling device 10 and cooled at a cooling rate of 1°C / s to obtain a nano-spinel material.
[0069] The main components of the selected aluminum ash are shown in Table 1:
[0070] Table 1
[0071]
[0072] The cross-sectional size of the mold for molding the green body of Examples 1-3 and Comparative Examples 1-5 was 20 mm × 15 mm, and the cut length during molding was 30 mm. The performance test results of the prepared finished products are shown in Table 1. The main test items include green body Cl content test, refractoriness test, shrinkage test, and heavy metal content test.
[0073] Green body Cl content detection: Undried green body is sampled and titrated to measure the green body Cl content;
[0074] Refractoriness test: The prepared nano-spinel material was reheated to 1300°C and above at five temperatures, with a heating rate of 20°C / min, to observe whether there was any change or damage;
[0075] Shrinkage rate detection: the volume change ratio of the prepared nano-spinel material and the green body;
[0076] Heavy metal content detection: The prepared nano-spinel material was crushed and obtained through fluorescence analysis.
[0077] The results are shown in Table 2.
[0078] Table 2
[0079]
[0080] From the analysis of the results of Examples 1-3 and Comparative Examples 1-6, the present solution can improve the refractoriness of the nano-spinel material and can remove heavy metals in the nano-spinel material.
[0081] Comparative Example 1 was not pretreated, and the halogens present in the aluminum ash caused the refractoriness to be lower than that of Example 1. Comparative Example 2 was not gas-washed, and the residual aluminate, ammonia and other substances may affect the starting temperature of the solid phase reaction. For example, the ammonium ions generated by the reaction of ammonia with the residual water of the secondary dehydration material will react with the residual calcium, magnesium, zinc and other ions to generate a low-melting complex, which advances the solid phase reaction, and the grains become coarse, which makes it easier to initiate cracks on the grain boundaries. The coarsening of the grains is also one of the reasons for the shrinkage of the nano-spinel material. The larger shrinkage can be used as a reference indicator for the reduction of refractoriness to a certain extent. At the same time, the aluminate is in a free state in the residual moisture of the secondary dehydration material, and it will segregate with the evaporation of water in the subsequent drying process, which will cause local abnormalities in the solid phase reaction, that is, introduce side reactions, and ultimately reduce the refractoriness of the nano-spinel material. While Example 1 can inhibit the complex reaction after gas washing, introduce carbonate, generate microporous structure during high temperature reaction, and inhibit crack expansion; at the same time, the aluminate is converted into aluminum hydroxide, which inhibits segregation, making the solid phase reaction more controllable and improving the refractoriness of the nano spinel material. Comparative Example 3 uses acetic acid, which is a monoprotic acid and cannot remove heavy metals. The effect of heavy metals on refractoriness may be because heavy metals will enter the spinel crystals during the high temperature solid phase reaction of the calcination process, causing the lattice to distort and easily become a crack source. And the higher the consistency of the phase composition of the nano spinel material, the higher the refractoriness, and heavy metal doping will lead to a decrease in consistency, especially the different thermal shrinkage properties of adjacent phases, which will lead to the initiation of microcracks during use. The citric acid selected in Example 1 has a polycarboxyl group, which can be complexed with heavy metals, and most of the heavy metal elements are removed during the dehydration process, so it has better refractoriness. Comparative Example 4 did not add starch, resulting in poor molding effect, so that there are certain microcracks on the surface of the green body after drying, which reduces the refractoriness. Comparative Examples 5 and 6 both have unreasonable calcination processes that result in low refractoriness. Comparative Example 5 cools faster than Example 1, and the surface shrinkage is inconsistent, resulting in stress, which in turn initiates microcracks; Comparative Example 6 generates too large grains compared to Example 1, as mentioned above, crack initiation and expansion are easier, and Comparative Example 6 has a low porosity, resulting in a worse thermal insulation effect of the nano-spinel material than Example 1.
Claims
1. A preparation process for producing nano spinel by harmless treatment of aluminum ash, characterized in that: The following steps are involved: Step (1) aluminum ash pretreatment: aluminum ash and water are added into a pretreatment barrel at a mass ratio of 1:10-15, stirred for reaction for 2-3 hours, and then dehydrated for the first time. After the first dehydration, the solid content is 85-90%, and the pretreated material is obtained; Step (2) batching: pour the pretreated material into a batching barrel, add 1-5% starch, 30-60% nano metal oxide particles, 10-15% aluminum sulfate, and 30-45% sodium aluminate based on the aluminum ash weight, add water to a solid content of 8-10%, add a pH adjuster, adjust the pH to 6-8, stir for 5-10 minutes, pass into a ball mill, add water, and mill for 1-3 hours, and obtain a secondary dehydrated material after a second dehydration; Step (3) air washing molding: introducing carbon dioxide into the secondary dehydrated material, followed by extrusion molding, and obtaining a green body after drying; Step (4) calcining: sending the green body into a calcining device for calcining, and obtaining the nano spinel material after cooling; In step (1), the nano metal oxide particles are one or more of nano magnesium oxide, nano zinc oxide, nano manganese oxide, and nano iron oxide; In step (2), the pH adjuster is citric acid; In step (3), the drying process is: drying at 50-60°C until the water content is less than 2%; In step (4), the calcination process is: heating from room temperature to 300°C at a rate of 3-5°C / min, heating from 300 to 1000°C at a rate of 5-8°C / min, heating from 1000 to final temperature at a rate of 8-15°C / min, and keeping warm for 10-30 minutes; the final temperature is 1250-1550°C; in step (4), the cooling rate is 0.5-5°C / s.
2. The process for preparing nano-spinel according to claim 1, characterized in that: In step (2), the secondary dehydration method is centrifugal dehydration, and the water content of the secondary dehydrated material is 5-10%.
3. An equipment for the preparation process of the nano-spinel according to any one of claims 1-2, characterized in that: The equipment comprises: a pretreatment barrel (1), a first dehydrator (2), a batching barrel (3), a ball mill (4), a second dehydrator (5), an air washing component (6), a molding device (7), a drying device (8), a calcining device (9), and a cooling device (10), which are connected in sequence according to the material flow order of the nano spinel preparation process; The pretreatment barrel (1) comprises a barrel body (1-5), a hot air pipe (1-3), an exhaust gas collection port (1-1), a feed port (1-2) and a discharge port (1-4); the hot air pipe (1-3) surrounds the barrel body (1-5); the feed port (1-2) is arranged at the upper end of the barrel body (1-5); and the discharge port (1-4) is arranged at the bottom of the barrel body (1-5); the exhaust gas collection port (1-1) is arranged at the top end of the barrel body (1-5); The hot air pipe (1-3) comprises an air inlet (1-3-1) connected to the cooling device (10) and an air outlet (1-3-2) connected to the drying device (8); The air washing component (6) comprises a horizontal auger (6-2) connected to the second dehydrator (5) and a cylinder (6-1) connected to the forming device (7); the horizontal auger (6-2) and the cylinder (6-1) are connected by welding; and a vent hole (6-3) is provided at the bottom of the cylinder (6-1).
4. The device according to claim 3, characterized in that The hot air pipe (1-3) is a semicircular pipe welded to the barrel body (1-5).
Citation Information
Patent Citations
Method for preparing nanometer gahnite
CN103449503A
Method for directly preparing aluminum spinel refractory from aluminum ash and material prepared by using method
CN105294135A
A method for preparing refractory materials from secondary aluminum ash
CN115947611B
Method for preparing magnesium aluminate spinel by using secondary aluminum ash
CN108585826A
Method of manufacturing refractory material by innocent treatment of secondary aluminum ash
CN111170750A
